Cerebral salt wasting syndrome following a traumatic frontal lobe hematoma : A case report - KC, Ram Bahadur; Kattel, Arati; Amatya, Prasanna Bahadur; Shrestha, Samrat (Journal of Advances in Internal Medicine, 2024)
BACKGROUND Cerebral Salt Wasting Syndrome (CSWS) is a rare complication of intracranial pathology characterized by hyponatremia and extracellular volume depletion. It is often confused with other sodium and water balance disorders, such as Syndrome of Inappropriate Antidiuretic Hormone Secretion (SIADH) and Central Diabetes Insipidus (CDI), making early diagnosis and appropriate management crucial. CASE PRESENTATION We present the case of a 68-year-old male with type 2 diabetes mellitus who suffered a traumatic frontal lobe hemorrhagic contusion following a fall. The patient developed polyuria and hyponatremia on the 6th day of admission, initially misdiagnosed as CDI and treated with desmopressin. However, despite treatment, his urine output continued to rise, and hyponatremia persisted. Subsequent evaluations, including urine and serum osmolarity, high urinary sodium levels, and imaging studies, led to the diagnosis of CSWS. Treatment was adjusted to include intravenous isotonic saline and fludrocortisone, significantly reducing urine output and correcting serum sodium levels. The patient was successfully discharged on the 25th day with stable electrolyte levels. CONCLUSION This case highlights the diagnostic challenges in differentiating CSWS from other sodium balance disorders, particularly CDI, in patients with traumatic brain injury. It emphasizes the importance of careful monitoring of urine and serum biochemistry, fluid status, and clinical progression to ensure accurate diagnosis and effective management. Early recognition and appropriate therapy for CSWS, including sodium and fluid replacement, can prevent further complications and improve patient outcomes.